Бухгалтерский и налоговый учет на производстве - Епифанов О. В. Олег Валерьевич; Терентьева Л. Ф. Людмила Фоминична; Васенко О. В. Ольга Владимировна; Захарова М. Н. Мария Николаевна (Москва, Альфа-Пресс, 2007)
Исключено из фонда НТБ ТПУ